Effects of various food components on the expansion, oil absorption, and crispiness of fried rice dough - Mohamed, Suhaila; Abd Hamid, Norhashimah (Universiti Putra Malaysia Press, 1994)
The physical characteristics offried dough were studied using model systems based on rice flours. Fried dough of maximum crispiness and minimum oil absorption were obtained from flour mixtures containing rice: glutinous rice in the ratio of 75:25 (amylose:amylopectin ratio = 9:69). Volume expansion and oil absorption of the finished product were found to be directly proportional to the amylopectin content and inversely proportional to the amylose content of the flour (r2 = 0.98 and 0.96 respectively). The best fitted lines for predicting the volume expansion and oil absorption offried dough are y = 120.6 + 7.16x and y = 23.4 + 0.15x respectively, where x is the amylopectin/amylose content of the whole flour. Amylose was found to increase hardness and reduce oil absorption of the fried product. Grispiness of the fried product was further improved by the addition of a little egg albumin, oil, GaGa] and pregelatinised rice flour. Although pregelatinised rice flour improved crispiness, it increased oil absorption. Oil absorption was reduced by the addition of 2.5 -5.5% oil and 4 -12% egg albumin to the flour.